PENERAPAN METODE ENVELOPING UNTUK MENDETEKSI CACAT LOKAL BANTALAN GELINDING - Abidin, Zainal; Bagiasna, Komang; Noviyantha, Wayan (Mesin, 2003)
This paper describes the study and implementation of enveloping method to detect a local bearing defect. First, it discusses the limitation of the conventional methode in bearing defect detention which is widely used in industry nowadays. The steps required to implement enveloping method are then studied and parameters influencing the success of detection process is identified. To demonstrate the effectiveness of the enveloping method, an experiment is performed to detect defect of a bearing with a simulated inner-race defect. The results of this study show that the enveloping method capable of detecting inner-race defect on a bearing in the situation where the conventional method fail to detect it.